Architecture of the Far East in the first third of the XX century - Алина Иванова (Проект Байкал, 2024)
The architecture of the Enlightenment is considered as a derivative of the architecture of the Far Eastern frontier, which consists of garrison and railway buildings. The article analyzes the projects of Far Eastern schools and colleges first identified in archival funds. To explain the phenomenon of “Russian style” schools, the author puts forward a version of the existence of a corporate “railroad Russian style” uniting a number of buildings from 1900 to 1926. Repeated elements speak of a plan, which was realized during a quarter of a century. The railway schools of the CER can be considered together with the Far Eastern railway stations as an integral part of a single ensemble.